Economic Role of Customs in The National Economy of Poland - Katarzyna SZMYD (Communications of International Proceedings, 2020)
The article is devoted to the economic role of customs duties in the national economy of Poland. The study also refers to the basic economic doctrines in the theory of foreign trade, but only from the point of view of customs issues (the role of customs). Issues related to the customs union and basic concepts in the field of customs were also discussed. Customs duties constitute one of the most important instruments of the state's economic policy, and have a significant impact on the structure of imports and its effectiveness, and constitute a source of budget revenues.
Keywords: customs; foreign trade; economy; European Union.